(untitled) (Bangladesh Journal of Nuclear Medicine, 2015)
Thyroid Hemiagenesis (THA) is a rare form of thyroid developmental anomaly. This developmental defect may or may not coincide with hormonal dysfunction. The detection of anomaly is quite incidental and infrequently found during investigations assessing thyroid functions. A three years old boy presented with gradual swelling in front of neck during last 2 months. He had no history of delayed milestones. Ultrasound imaging and thyroid scan by 99m -Technetium- pertechnetate revealed hemi agenetic development of left lobe of thyroid gland. His biochemical assessment showed euthyroid state. He had positive family history with hypothyroid maternal grandmother and congenital hypothyroid maternal cousin. Ultrasonography and thyroid scan are useful tools for demonstrating this form of dysgenesis of thyroid gland. Follow up monitoring of thyroid function at regular interval in children with congenital anomaly of thyroid gland should be done to take timely measures, if required. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22501 Bangladesh J. Nuclear Med. 17(1): 104-110, January 2014